The Role of Tourism in Achieving Regional Fiscal Independence and Community Welfare - I Made Jyotisa Adi Dwipatna; Achmad Solihin (Yayasan Riset dan Pengembangan Intelektual, 2023)
A shift in governance system from centralization to decentralization occurs during the era of regional autonomy that drives regional government to explore and develop the regional potentials in order to make regions be able to independently administer their government. This study is aimed to analyzed the role of the tourism sector in achieving regional fiscal independence and its impact towards community welfare. This study used panel data from 9 regencies/city in Bali Province that covered the period from 2013 to 2020 and were estimated through Partial Least Square-Structural Equation Modelling (PLS-SEM) analysis method. The result shows that the tourism sector has a vital role in achieving regional fiscal independence. The increase in number of tourist visits results in tax revenues and tourism sector retribution that contribute to the local own source revenue. This revenue is subsequently able to be utilized as regional government to finance infrastructure development that will enhance public services and eventually improve the community welfare.